Author Correction: Tonic excitation by astrocytic GABA causes neuropathic pain by augmenting neuronal activity and glucose metabolism (vol 56, pg 1193-1205 ,year 2024) - Ju, Yeon Ha; Cho, Jongwook; Park, Ji-Young; Kim, Hyunjin; Hong, Eun-Bin; Park, Ki Duk; Lee, C. Justin; Chung, Euiheon; Kim, Hyoung-Ihl; Nam, Min-Ho (Springer Nature, 2024)
After online publication of this article, the authors noticed an error in the author list. “Ki Duk Park” should have been inserted as a co-author to the author list and “Center for Brain Function” should be removed from the Affiliation 1. The authors apologize for any inconvenience caused. The original article has been corrected.